Effects of total parenteral nutrition containing essential trace elements on their concentrations in rats - Matsuda, A; Kimura, M; Yokoi, K; Kabata, H; Itokawa, Y; Kataoka, M; Sato, M (Nippon eiseigaku zasshi, 1989)
Twenty-four rats were equally divided into 4 groups and maintained for 1 week as follows: Group A (normal control) with a synthetic normal diet and distilled water, group B with conventional total parenteral nutrition (TPN), i.e., TPN without essential trace elements (ETE), group C with TPN supplemented with a usual dose of ETE solution (TE-5), and group D with TPN supplemented with 3 times the usual dose of TE-5. Body weight, trace element concentrations in various tissues and certain blood biochemical parameters were determined in these rats. The results were as follows: 1) No significant differences in body weight were observed among the groups. 2) The iron concentrations in plasma and tibia decreased significantly in group B as compared with group A. The addition of TE-5 prevented these decreases, but dose-dependent increases in the concentrations of iron were observed in liver, spleen and kidney (groups C and D). 3) The zinc concentrations in plasma, whole blood, brain, heart, kidney and tibia decreased significantly in group B as compared with group A. The addition of TE-5 prevented these decreases dose-dependently (groups C and D). 4) The copper concentrations in plasma, whole blood, liver, spleen, kidney, testis and tibia decreased significantly in group B as compared with group A. The addition of TE-5 resulted in a tendency for these decreases to diminish (groups C and D). 5) The manganese concentrations of whole blood in group B decreased significantly as compared with group A. The addition of TE-5 caused the manganese concentrations of various tissues in groups C and D to increase significantly as compared with group A.(ABSTRACT TRUNCATED AT 250 WORDS)